Florida ethnobotany : Fairchild Tropical Garden, Coral Gables, Florida Arizona-Sonora Desert Museum, Tucson, Arizona : with more than 500 species illustrated by Penelope N. Honychurch [and others] /: Fairchild Tropical Garden, Coral Gables, Florida Arizona-Sonora Desert Museum, Tucson, Arizona : with more than 500 species illustrated by Penelope N. Honychurch [and others]. (2004) - Unknown
No abstract available